Preponderance of the evidence versus intime conviction: a behavioural perspective on a conflict between American and continental European law - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2008)
Most apparent differences between US and continental law lose their relevance once one looks beneath the doctrinal surface and checks how doctrine plays itself out in concrete cases. One of the few exceptions is standards of proof. Not only distinguishes US law between preponderance of the evidence and beyond a reasonable doubt. It even constructs proof differently. In the US, proof is an objective, science-like affair. On the continent, proof is holistic and subjective. The decision maker is called upon to form a personal conviction, and to take on personal responsibility for her assessment of the facts. What seems utterly mystic actually has a sound scientific base. Continental law capitalises on the power of intuition. Intuition relies on unconscious mental machinery. This apparatus processes huge amounts of information in almost no time. It is programmed to come up with an assessment even if the evidence is patently incomplete. It does so by multiple feedback loops. At the end of this procedure, evidence conflicting with the final decision is devalued, whereas evidence supporting the decision is given greater weight. While instrumental in making most of the available evidence, the mental mechanism is not error proof. One particularly troublesome implication precisely concerns standards of proof. Given the mechanism is designed to force a decision, one might be afraid that it mutes the difference between standards of proof. A more stringent standard would be neutralised by an even stronger devaluation of conflicting evidence. Happily an experiment shows that the concern is misplaced. A plausible explanation is this: the standard of proof instruction tags convicting an innocent defendant by a somatic marker. If this hypothesis could be proven true, the presumption of innocence would have been rescued by an emotion.
Keywords: 340; Common Law; Rechtsordnung; Verhalten; Test; Vergleich; USA; Europa